ANALISIS PENGELOLAAN SISTEM PENYIMPANAN DAN PEMINJAMAN ARSIP PADA PT HEXINDO ADIPERKASA TBK CABANG PALEMBANG - Sri Porwani (Politeknik Negeri Sriwijaya, 2012)
Mail filling is such an activity related to receiving, recording, delivery and destruction of correspondence or a variety of other records. Filing is one of the areas of administration that manages a variety of information for the development and progress of a company or organization. This study aims at determine the purpose of a good archival storage system is implemented and to determining borrowing Systems archive Tbk PT Hexindo Adiperkasa Palembang Branch. While the object of research conducted at the Branch Tbk PT Hexindo Adiperkasa Palembang. The company was engaged in the heavy equipment industry. In collecting data using primary data and secondary data obtained with the method of collecting data through interviews, observation, questionnaires, and literature. Based on this study it was found that the archive storage systems and lending to PT Tbk Hexindo Adiperkasa Palembang Branch, there are still obstacles that lack of good administration section archival storage system, and the absence of lending form to records. Thus, the authors provided a solution in the storage system should be better storage system combined with other systems, such as systems that region to facilitate staff in finding a searchable archive, as well as a form of borrowing that serves as evidence of the loan files, so it be could known who borrowed archives corresponding information contained in the archives borrowed time.